The Effect of Job Rotation on Career Management (Malaysian Management Journal, 2015)
Job rotation is a type of on-the-job training where an employee is encouraged to gain a range of information, skills and competencies in the workplace. The purpose of this study is to examine the influence of job rotation on career management. Toward this objective, a survey was carried out amongst 76 assistant registrars in one public university in Malaysia. Factor analysis has revealed that there are three distinct dimensions of job rotation, namely, business knowledge, technical knowledge and administrative knowledge, as well as a single dimension of career management. Multiple regression results shows that only two dimensions of job rotation have significantly influence on career management, with the exception of business knowledge. This finding has also indicated that job rotation practice affects the career management through the enhancement and enrichment of employees’ knowledge and skills, which in turn will influence their career progression in the workplace.